2022
DOI: 10.3390/biomedicines10123249
|View full text |Cite
|
Sign up to set email alerts
|

Pyrvinium Pamoate: Past, Present, and Future as an Anti-Cancer Drug

Abstract: Pyrvinium, a lipophilic cation belonging to the cyanine dye family, has been used in the clinic as a safe and effective anthelminthic for over 70 years. Its structure, similar to some polyaminopyrimidines and mitochondrial-targeting peptoids, has been linked with mitochondrial localization and targeting. Over the past two decades, increasing evidence has emerged showing pyrvinium to be a strong anti-cancer molecule in various human cancers in vitro and in vivo. This efficacy against cancers has been attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 141 publications
1
14
0
Order By: Relevance
“…In preclinical models, PP exhibited strong efficacy in protecting against both tauopathy and retinal degeneration at nanomolar concentration. We further demonstrated that the previously known anti-YAP/WNT activity of PP [21][22][23] could be explained by the expanded proteostasis framework and is also required for its ability to ameliorate proteinopathies. Lastly, we showed that both the reduction of proteostasis gene expression and increase of YAP1 transcriptional activity is associated with retinal degeneration in mice and tauopathy in humans.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…In preclinical models, PP exhibited strong efficacy in protecting against both tauopathy and retinal degeneration at nanomolar concentration. We further demonstrated that the previously known anti-YAP/WNT activity of PP [21][22][23] could be explained by the expanded proteostasis framework and is also required for its ability to ameliorate proteinopathies. Lastly, we showed that both the reduction of proteostasis gene expression and increase of YAP1 transcriptional activity is associated with retinal degeneration in mice and tauopathy in humans.…”
Section: Introductionmentioning
confidence: 71%
“…Interestingly, pyrvinium is enriched with cationic amines and aromatic motifs, chemical features that were predicted to partition into various nuclear condensates 99 . PP was originally developed as an anthelmintic drug effective for treating pinworm infections 100 . Moreover, it has gained strong recent interest as an anti-cancer reagent due to its ability to inhibit WNT signaling 100 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrvinium pamoate (PP): The antifungal and anthelmintic PP, approved by the FDA ( Li et al, 2022 ), was investigated as an anti-cancer drug and found to act via multiple pathways such as WNT signaling, inhibition of mitochondrial NADH-fumarate, tumor stemness, the unfolded protein response and hedgehog signaling ( Schultz and Nevler, 2022 ). In our screen, PP caused a significant decrease in HR in both heart chambers (−8.54; n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggest that, although p53 activation plays a significant role in cell apoptosis during pyrvinium treatment, there are also p53-independent pro-apoptotic mechanisms that provide pyrvinium with an advantage as a novel therapy for treating p53 mut or p53 -/-MCC. Pyrvinium has been previously identified as a mitochondrial inhibitor and has demonstrated even greater potency in nutrient-deficient conditions (36,37,70). To assess the extent of oxidative phosphorylation inhibition by pyrvinium in MCC cells, we conducted an FCCP-OCR analysis using the Seahorse XF96 Analyzer.…”
Section: Pyrvinium Pamoate Impacts Canonical and Non-canonical Wnt Si...mentioning
confidence: 99%